Strongly M_φM_ψ-convex functions, the Hermite-Hadamard-Fejér inequality and related results - Bombardelli, Mea; Varošanec, Sanja (Annales Mathematicae Silesianae, 2023)
We present Hermite-Hadamard-Fejér type inequalities for strongly MφMψ-convex functions. Some refinements of them and bounds for the integral mean of the product of two functions are also obtained.